2017
DOI: 10.3390/ijerph14111314
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function Capacities, Negative Driving Behavior and Crashes in Young Drivers

Abstract: Motor vehicle crashes remain a leading cause of injury and death in adolescents, with teen drivers three times more likely to be in a fatal crash when compared to adults. One potential contributing risk factor is the ongoing development of executive functioning with maturation of the frontal lobe through adolescence and into early adulthood. Atypical development resulting in poor or impaired executive functioning (as in Attention-Deficit/Hyperactivity Disorder) has been associated with risky driving and crash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 63 publications
(141 reference statements)
5
60
0
2
Order By: Relevance
“…Based on our understanding of EF, which aligns with the framework by Miyake et al (2000), a recent review by Walshe et al (2017) stated that, out of the three core components of EF, working memory, inhibition, and set shifting, the latter was reported only in very few studies and none found a relationship with driving performance in a driving simulation. In contrast, inhibition, particularly in combination with working memory, responsible for governing multitasking, seems to be related to driving performance (Walshe et al, 2017). For example, Ross et al (2015) showed that poor performance on inhibitory tasks and poor working memory together contributed to unsteady driving performance.…”
Section: Introductionmentioning
confidence: 90%
“…Based on our understanding of EF, which aligns with the framework by Miyake et al (2000), a recent review by Walshe et al (2017) stated that, out of the three core components of EF, working memory, inhibition, and set shifting, the latter was reported only in very few studies and none found a relationship with driving performance in a driving simulation. In contrast, inhibition, particularly in combination with working memory, responsible for governing multitasking, seems to be related to driving performance (Walshe et al, 2017). For example, Ross et al (2015) showed that poor performance on inhibitory tasks and poor working memory together contributed to unsteady driving performance.…”
Section: Introductionmentioning
confidence: 90%
“…42 Teenagers develop executive functioning skills as the frontal lobe of their brain matures into early adulthood. 43 During this time, vehicle collisions tend to decline and plateau at the age of 25. 44 The review in this section includes the four elements of executive functioning-working memory, inhibitory control, cognitive flexibility, and emotion regulation-that are identified most frequently in the literature on autism and driving.…”
Section: Diagnostic Challenges and Their Potential Effect On Drimentioning
confidence: 99%
“…Dalam psikologi lalu lintas ada sejumlah teori besar mengulas mengenai kontribusi atensi, memori, dan tentu saja spatial cognition pada perilaku mengendarai kendaraan bermotor (Trif, 2015). Spatial cognition merupakan kemampuan dalam membuat terkaan ketika di jalan raya, maintaining dan fokus pada beberapa stimulus termasuk jarak dan kecepatan, melakukan kontrol diri dan berpindah dari satu atensi objek ke yang lain (Walshe, McIntosh, Romer, & Winston, 2017 (Leather, 2009).…”
Section: Kata Kunci: Kognisi Spasial; Psikologi Lalu Lintas; Berkendaraunclassified